The Context-dependence of Questions and Answers - van Rooy, Rober (Proceedings of the Amsterdam Colloquium, 1997)
The appropriateness and content of questions and answers depends on context. In this paper a dynamic semantics if formulated in which context contain enough information about the discourse to determine what is expressed by questions and answers, and enough information about what is presupposed about the subject matter of conversation to determine their appropriateness. It is proposed that mention-all and mention-some questions introduce not only partitions to the context, but also that they make the context-depenent abstracts that underlies these partitions anaphorically accessible. The latter information about the discourse is needed to determine what is expressed by an answer. These abstracts are also used to determine the (default) exhaustive interpretation of focused constituents, and the (default) non-exhaustive interpretation of topical constituents.